Web-based learning media the skills of suturing rupture perineum of midwifery students - Nurul Fitrahminarsih N; Syafruddin Syarif; Mardiana Ahmad; Budu; Yusring Sanusi B (Elsevier, 2021)
Objective: This research aims to determine the influence of Web-based learning media on improving perineum rupture stitching skills for D-III Midwifery students. Method: This study uses a Research and Development (R&D) research design with the Borg & Gall development model to test the use of this product. The Quasi-Experimental research with a non-equivalent control group design was conducted in January-February 2020 at AKBID Pelamonia Makassar. The sample in this study was the second semester of the Midwifery Academy Pelamonia VII Wirabuana Makassar, totaling 64 people who were divided into two groups of intervention and control. The intervention group I (WEB media giving) amounted to 32 people and control 32 people. The sampling technique used is purposive sampling. At the end of the meeting, a post-test was conducted. The statistical test used was the paired sample t-test and Wilcoxon test. Results: The percentage of application assessment using the Technology Acceptance Model (TAM) questionnaire to assess the application's usability level is a very good category and can be interpreted that students accept WEB-based learning media. Statistical tests showed differences in the results of measurement I and measurement II in the removal of grade II perineum rupture in the control group (p < 0.05) and contributed 15.6%. In the intervention group I (WEB-based learning media), there were differences in skills before and after media giving (p < 0.05) and contributed 89.8% in improving the skills of the second semester Midwifery DIII students regarding the sewing of second-degree perineum rupture. Conclusion: The use of Web-Based Learning Media facilitates and enhances students in performing second-degree perineum rupture sewing skills.